Blood pressure variability and cognitive dysfunction: A systematic review and meta‐analysis of longitudinal cohort studies - Chiu, Tzu‐Jung; Yeh, Jiunn‐Tyng; Huang, Chi‐Jung; Chiang, Chern‐En; Sung, Shih‐Hsien; Chen, Chen‐Huan; Cheng, Hao‐Min (The journal of clinical hypertension (Greenwich, Conn.), 2021)
The variability of blood pressure (BPV) has been suggested as a clinical indicator for cognitive dysfunction, yet the results from clinical studies are variable. This study investigated the relationship between BPV and the risk of cognitive decline or dementia. Bibliographic databases, including PubMed, Scopus, and Embase, were searched systematically for longitudinal cohort studies with BPV measurements and neuropsychological examinations or dementia diagnosis. A traditional meta‐analysis with subgroup analysis, and a further dose‐response meta‐analysis were conducted. Twenty cohort studies with 7 924 168 persons were included in this review. The results showed that a higher systolic BPV (SBPV), when measured with the coefficient of variation (SBP‐CV) or standard deviation (SBP‐SD), was associated with a higher risk of all‐cause dementia diagnosis but not incidence of cognitive decline on neuropsychological examinations. In subgroup analysis, the effect was more prominent when using BPV of shorter timeframes, during shorter follow‐ups, or among the elderly aged more than 65 years. No dose‐response relationship could be found. Our study suggested possible positive associations between SBPV and the risk of dementia. Further studies are required to validate these findings.